LATE DEVONIAN CONODONTS FROM THE HOJEDK SECTION, KERMAN PROVINCE, SOUTHEASTERN IRAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Conodonts (34 species and subspecies) from the Hojedk section north of Kerman span the late Givetian to early Famennian. The new data suggest that Devonian biostromes in central and eastern Iran were deposited on differing levels, and that the currently accepted ranges of Icriodus excavatus, Polygnathus subincompletus and P. mosquensis are late Givetian - late Frasnian, early to late Frasnian, and middle to late Frasnian. Polygnathus ashourii n. sp. is proposed.
Keywords: Conodonts; Biostratigraphy; Devonian; Kerman